The Implementation of Project Based Learning to Improve Students’ Writing Skill - Oroh, Elisabeth Z.; Wilar, Blessy Monique (Journal of English Language Teaching, Literature and Culture, 2022)
The aim of this study to improve students’ writing skill especially for students in SMA Negeri 2 Manado X Ipa 1. The subject of this study is the 36 students in X Ipa 1 SMA Negeri 2 Manado. Utilized data collection techniques include observation, testing, and documentation. The first cycle of students’ learning describes a tourist destination. Students have challenges in verbal and non-linguistic domains (courage, honesty, and attitude, respectively). On the second cycle, they describe a destination for tourists. Cycle II focuses more on linguistic (vocabulary, structure, and punctuation) and non-linguistic (fluency and mastery of language) qualities that are still deficient. Planning assessment, implementation evaluation, and project evaluation (contain, organization, vocabulary, grammar, and mechanics) were deemed adequate for this study. The results of a test measuring kids’ writing skills indicate an increase. The increase occurred as follows: (1) the average pre-cycle value of 72.75 increased to 78.06; (2) the average evaluation value of the first cycle was 78.06 with a completeness percentage of 50 percent; and (3) the average evaluation value of the second cycle is 84.46 with a completeness percentage of 84.37 percent.